Isolation And Identification Of Some Pathogenic Bacteria And Fungi From Restaurantes And Meat Shop’s In Al-Samawa City - Yaseen, Hasanain Marzoq (University of Thi-Qar Journal of Science, 2019)
The present study include isolation and identification of some pathogenic fungi and bacteria fromrestaurant and meat shop’s in AL-Samawa city by taking samples from 15 restaurants and 15 meat shop’s,choose randomly with three replicates for each sample on solid culture medium Potato’s Dextrose Agar (PDA)for fungi and Nutrient Agar for bacteria. The results showed several fungal and bacterial species were isolatedfrom these places, for restaurants fungal species were: Rhizopus stolanifer, Penicillium notatum, Fusariumoxysporum, Alternaria alternata, Aspergillus niger, Rhizoctonia solani, Cladosporium sp. and Aspergillusflavus, with percentage of frequency which has (21.78, 10.89, 7.92, 8.91, 18.81, 7.92, 6.93 and 16.83)%respectively, while the bacterial species were: Bacillus cereus, Clostridium botulinum , Escherichia coli,Salmonella typhi, Shigella dysenteriae, Staphylococcus aureus and Lactobacillus subtilus (12.16, 9.45, 21.62,18.91, 16.21, 12.16 and 9.45)% respectively. From meat shop’s the isolated fungal species were: Aspergillusniger, Penicillium notatum, Aspergillus flavus, Rhizopus stolanifer and Cladosporium sp. (23.91, 16.30,19.56, 28.26 and 11.95)% respectively, while the isolated bacterial species were: Salmonella typhi,Staphylococcus aureus ,Lactobacillus subtilus, Pseudomonas aeruginosa, Escherichia coli and Clostridiumperfringens (15.87, 19.04, 17.46, 9.52, 23.80 and 14.28)% respectively.